Systematic Literature Review: Work Engagement Program to Improve Millennial Employee Performance - Tedi, Setiawan; Agus, Rahayu; Lili Adi, Wibowo; Erwin, Yulianto (INTI International University, 2022)
In the digital era, the banking industry needs employees who are able to work with growth mindset in an environment that is agile and digital savvy. work engagement is the attitude and behavior of individuals in carrying out their work roles by expressing themselves completely physically, cognitively, affectively, and emotionally. The most compatible work engagement program for the millennial generation workforce is the key to the success of the banking industry in winning the highly competitive business world in the Industrial Revolution era 4.0. and Society 5.0. The purpose of this research is to identify, review and analyze the Work Engagement Program to Improve Employee Performance in the Banking Industry. The research method used is a Systematic Literature Review of relevant research. There are two Research Questions (RQ) set in this research. The research conducted concluded that the right work engagement program makes Millennial employees in the banking industry find meaning in their work, and gain pride as part of the workplace to jointly achieve the company's vision and mission. Each employee will go the extra mile and strive for work results to be above what is expected in time and energy characterized by vigor, dedication, and absorption.